Rhetorical Moves of Research Article Abstract in Linguistics and Language Journals with Different Quartile Value - Triyanna, Wahyuni; Harahap, Alamsyah; Yunita, Wisma (UNIB Press, 2025)
Writing an abstract in a research article is very important. The existence of abstract is compulsory within a research article. It is a research summary that must be attached and presented with the article. This study aims to find out moves and the most common pattern in RA abstracts in linguistic and language journals with different quartiles value. By using descriptive qualitative method, eighty RA abstract of linguistic and language journals with different quartile value were extracted from eight journals. Namely: Journal of Second Language Writing, Studies in English Language Education, 3L: Language, Linguistics, Literature, Applied Research on English Language, JALT Journal, World Journal of English Language, Research in Language, Suvannabhumi. The result finding; 1) Move 2 (Aim/Purpose) exists in seventy RA abstracts, Move 3 (Method) is present in sixty two RA abstracts, and Move 4 (Finding/Result) appears in Seventy Eight RA abstracts. In contrast, Move 1 (Introduction) is found in only 50 RA abstracts, and Move 5 (Conclusion) appears in 31 RA abstracts. 2) Q1 journal have the most frequent move, indicating a more comprehensive and detailed structure in their abstracts. In contrast, journals in lower quartiles, such as Q3 and Q4, often feature abstracts with fewer moves. As this study focuses only on the rhetorical move and pattern of RA abstract in field of linguistic and language journal with different quartile value, future research should conduct a comparative study and language features of the RA abstract in the field of across discipline with different quartile value.